EVALUASI EFEKTIVITAS PENGURANGAN DAN PENAMBAHAN SUHU PREHEAT DALAM PROSES WELD REPAIR PADA MATERIAL BAJA KARBON API 2W GRADE 50 DITINJAU DARI CACAT LAS DAN KEKERASAN - Sugiono; Susilo, Trisno; Adi, Fajar Tyas (UNIMAR AMNI Semarang, 2025)
This research aims to evaluate the effectiveness of reducing and increasing preheat temperature in the welding repair process on API 2W grade 50 carbon steel material using a stick welding process or Shielding metal arc welding (SMAW). A number of test samples were prepared with varying preheat temperatures of 350C, 650C and 950C with the same welding parameters.This test is carried out by applying a non-destructive test (NDT) and hardness test to reduce the effectiveness of reducing and adding preheat temperature to the welding results after the weld repair process. The results of this research can provide useful guidance or references for students, campuses and the industrial world in minimizing the occurrence of weld defects and knowing the hardness value of API 2W grade 50 material after the weld repair process at companies in future projects